The Art of Influence: Analyzing Xi Jinping's Illocutionary Speech Acts at Bo’ao Asia Forum 2022 - Muhammad Farhan Masrur; Berliana Ulfa Faizah; Nisrina Ikananda Rahmanita; Tirza Anugerah Putri Mulia Rajagukguk; Shaoqin Xiang (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
This research investigates the illocutionary speech acts utilized by Xi Jinping in his keynote speech at the Bo’ao Asia Forum 2022. The study aims to categorize and analyze the specific types of illocutionary speech acts used by Xi Jinping in his address titled "The World in COVID-19 & Beyond: Working Together for Global Development and Shared Future." Employing a qualitative-descriptive research methodology, the study focuses on the role of language in speech acts as a means to convey the intended message to the audience. The analysis identifies four distinct types of illocutionary speech acts in Xi Jinping's speech: assertive acts (showing, stating, reporting), directive acts (advising, inviting, instructing), commissioner acts (proposing, promising), and expressive acts (greeting, welcoming, complaining, thanking). By exploring these illocutionary speech acts, the research sheds light on Xi Jinping's effective communication strategies and his ability to engage and influence the audience during the Bo’ao Asia Forum 2022. The findings contribute to a deeper understanding of the persuasive power of language in high-profile speeches and the art of effective public speaking.Key Words: Speech, Illocutionary Speech Act, Xi Jinping, Bo’ao Asia Forum.